New investigations of the 10B(p, )7Be reaction at bombarding energies between 0.6 and 1 MeV. (23rd February 2016) - Lombardo, I; Dell'Aquila, D; Conte, F; Francalanza, L; Cognata, M La; Lamia, L; Torre, R La; Spadaccini, G; Spitaleri, C; Vigilante, M
Abstract: We measured the 10 B(p, ) 7 Be reaction in the bombarding energy domain of 0.6-1.0 MeV, a region where very few data (with large uncertainties) have been reported in the literature. Despite the experimental difficulties, due to the unfavourable reaction kinematics and the presence of contaminants in the 10 B target, we were able to measure excitation functions at both forward and backward angles thanks to the use of the inverse absorber technique . The obtained angular distributions show a continuous shape evolution, testifying to the contributions of several resonant states in the 11 C compound nucleus. An R -matrix analysis of some reaction and scattering channels allows us to refine the spectroscopy of 11 C excited states.